Effect of Al(OH)2 and Mg (OH)2 Suspension Dosage Form on the Absorption of Oral Ciprofloxacin - Budiatin, Aniek Setiya (2008)
Potential interaction of fluroquinolone with other drugs have been established in the several reports. The absorption of fluroquinolones were almost entirely inhibited by concomitant administration of di and trivalent cations such magnesium and aluminium in the antacids were significantly decreased the absorption of ciprofloxacin through formation of a complex. The effect of antacid (Antasida DOEN) 1.4 ml/kg body weight doses which containing polyvalent cation Mg (OH) 2 and Al(OH) 3 on the absorption of ciprofloxacin. were examed in healthy rabbit. Twelve subjects were given 23 mg/ml BW ciprofloxacin alone as control. On day 8 the six subjects were given antacid and ciprofloxacin concomitant and the other were given antacid two hours after ciprofloxacin. The absorption parameters of ciprofloxacin were determined by spectrofluorometric method. Those parameters were Cmax, tmax and AUC, the administration of ciprofloxacin and antacids concomitantly result Cmax, tmax and AUC were 1.27±0.45g/ml; 110±48.99 minutes and 248.63±94.77g.minutes/ml respectively in a significant decrease in ciprofloxacin absorption (p<0.05) and the administration of antacids two hours after ciprofloxacin result Cmax, tmax and AUC were 1.37±0.65g/ml;75±36.74 minutes and 245.09±100.46 g.minutes/ml respectively in a significant decrease in ciprofloxacin absorption (p<0.05). Percentages of relative bioavailability compared with control values were 27.06±16.70% and 8.77±6.97% for concomitant and two hours after ciprofloxacin respectively.